2018
DOI: 10.1128/jb.00774-17
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the (Almost) Unknown: Archaeal Two-Component Systems

Abstract: 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Since the prrAB regulon and the environmental cue which stimulates PrrAB activity are unknown, a global transcriptomics approach was used to analyze differential gene expression in standard laboratory growth conditions. RNA-seq was used to determine transcriptional differences between the ΔprrAB mutant, mc 2 155, and the complementation strains during mid exponential growth, corresponding to an OD 600 of~0.6 (See Additional file 1: Figure S3), in supplemented Middlebrook 7H9 (M7H9) broth. Total RNA was isolated from three independent, biological replicates of each M. smegmatis strain.…”
Section: Transcriptomics Analysis Of the M Smegmatis Wt δPrrab Mutant And Complementation Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the prrAB regulon and the environmental cue which stimulates PrrAB activity are unknown, a global transcriptomics approach was used to analyze differential gene expression in standard laboratory growth conditions. RNA-seq was used to determine transcriptional differences between the ΔprrAB mutant, mc 2 155, and the complementation strains during mid exponential growth, corresponding to an OD 600 of~0.6 (See Additional file 1: Figure S3), in supplemented Middlebrook 7H9 (M7H9) broth. Total RNA was isolated from three independent, biological replicates of each M. smegmatis strain.…”
Section: Transcriptomics Analysis Of the M Smegmatis Wt δPrrab Mutant And Complementation Strainsmentioning
confidence: 99%
“…Mycobacterium smegmatis strain mc 2 155 [18] is a non-pathogenic, rapid-growing, saprophytic mycobacterium that is used as a surrogate model to study M. tuberculosis genetics and mycobacterial TCSs. We recently demonstrated that prrAB is not essential in M. smegmatis and that PrrAB differentially regulates triacylglycerol biosynthetic genes during ammonium limitation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Two-component systems (TCSs) participate in signal transduction pathways and are ubiquitously found in bacteria, archaea, some lower eukaryotes and plants [1][2][3][4]. TCSs recognize specific environmental stimuli [5] and integrate an adaptive response, frequently by modulating transcription [6].…”
Section: Introductionmentioning
confidence: 99%
“…Two-component systems (TCSs) participate in signal transduction pathways and are ubiquitously found in bacteria, archaea, some lower eukaryotes and plants [1][2][3][4]. TCSs recognize specific environmental stimuli [5] and integrate an adaptive response, frequently by modulating transcription [6].…”
Section: Introductionmentioning
confidence: 99%